Clinical and biological profile of Sickle Cell Anemia children in a rural area in Central Africa. Issue 1 (31st December 2023) - Mbayabo, Gloire; Ngole, Mamy; Lumbala, Paul Kabuyi; Lumaka, Aimé; Race, Valerie; Matthijs, Gert; Mikobi, Tite Minga; Devriendt, Koenraad; Van Geet, Chris; Lukusa, Prosper Tshilobo
ABSTRACT: Background: Sickle Cell Anemia (SCA) is the most common genetic disease worldwide caused by a single mutation in the gene HBB . The disease severity is very variable and depends on many factors. We evaluated the clinical and biological profile of sickle cell anemia children in rural Central Africa. Methods: This cross-sectional study was conducted in the Hôpital Saint Luc de Kisantu, located 120 km away from Kinshasa-DR Congo in an area of 35 km around Kisantu with a population of roughly 80 000 individuals. We included SCA patients aged 6 months to 18 years. We collected clinical and hematological data. The SCA scoring system proposed by Adegoke et al. in 2013 was applied to determine the disease severity. We searched for factors associated to the disease severity. Results: This study included 136 patients, 66 males and 70 females (sex-ratio M/F 0.94). The mean severity score was 8.21 ± 5.30 (ranges 0–23). Fifty-nine (43.4%) children had mild disease, 62 (45.6%) moderate and 15 (11%) severe disease. Girls had higher levels of HbF than boys ( p  = 0.003). An inverse correlation was observed between fetal hemoglobin and the disease severity ( p  = 0.005, r −0.239, IC95% −6.139; −1.469). Some factors such age influence the occurrence of certain chronic complications such as avascular bone necrosis. Conclusion: In conclusion, the disease severity of SCA depends on multiple factors. In this study, fetal hemoglobin was the main modulator of the disease severity. These data may also serve as a baseline to initiate HU treatment in this setting. GRAPHICAL ABSTRACT: UF0001